Shaft alignment handbook - Piotrowski, John, 1952- (Mechanical engineering (Taylor & Francis), 2007)
Now in its third edition, Piotrowski's bestselling Shaft Alignment Handbook is still the most trusted and widely embraced guide in the field. This edition was reorganized, updated, and expanded to be more convenient, intuitive, and to reflect the latest developments in the area. Dedicated chapters now discuss the basics of modeling, each of the five basic alignment methods, and electro-optic methods. Significant new material reflects recent findings on detecting misalignment, machinery movement from offline to running conditions, multiple element drive trains, and specific types of rotating ma.